The Role of Sentinel Lymph Node Biopsy in the Management of Breast Cancer - Saha, Moni Mohan; Hossain, Md Mokter; Saha, Sukumar (Journal of Bangladesh College of Physicians and Surgeons, 2015)
The sentinel lymph node (SLN) is defined as the first node(s) receiving lymphatic drainage from a primary tumour. A promising alternative to axillary lymph node dissection (ALND) is sentinel lymph node biopsy. SLN biopsy has been introduced as a technique to identify axillary lymph node most likely to contain tumour cells metastasizing from a primary carcinoma of breast. Several methods of identifying the SLN exists, including the use of radioactive tracer, lymphazurin dye or combination of the two via intraparenchymal and/or intradermal, peritumoral or periaerolar injection sites. Intraoperative evaluation of SLNs are done by performing FS(Frozen Section) on all the lymph nodes after serially sectioning them at 3-4mm intervals; at least 2 levels are cut of all the sentinel lymph nodes. In addition, touch preparation cytology(TP) smear may also be made for evaluation. The limitations of SLNB is that a proportion of patients who have metastasis limited to the SLN can be predicted when there is a combination of tumour size <1.0cm, the absence of lymphovascular invasion and micrometastatic disease (<0.2cm) in SLN. However for patients with large breast cancer, the role of SLNB is controversial. Early studies of SLNB in large breast cancer patients demonstrated a high (8-18%) false negative rate, with the accuracy worsening with the increasing size. Excision of SLNs have an extremely low morbidity and a high degree of staging accuracy. A tumour-free SLN virtually excludes lymphatic involvement of the entire regional lymphatic basin. More than 50 observational studies of SLNB validated by a back up ALND demonstrate that SLNB is feasible, accurate and suitable for virtually all patients with operable clinically node negative disease. Sentinel lymph node biopsy not only provide prognostic information, but also aims to guide adjuvant therapy without the untoward side effects of complete axillary dissection. J Bangladesh Coll Phys Surg 2014; 32: 211-217